Association Between Mobile App Use and Caregivers' Support System, Time Spent on Caregiving, and Perceived Well-being: Survey Study From a Large Employer - Pelin Ozluk; Rebecca Cobb; Alyson Hoots; Malgorzata Sylwestrzak (JMIR Publications, 2022)
BackgroundMobile technology to address caregiver needs has been on the rise. There is limited evidence of effectiveness of such technologies on caregiver experiences. ObjectiveThis study evaluates the effectiveness of ianacare, a mobile app, among employees of a large employer. ianacare mobilizes personal social circles to help with everyday tasks. Through the use of ianacare, we evaluate the associations between coordinating caregiving tasks among a caregiver's personal support network and outcomes related to the caregiver's support system, time use, perceived productivity, and perceived health and well-being. Caregiver tasks include tasks such as meal preparation, respite care, pet care, and transportation. Time use is the measure of a caregiver's time spent on caregiving tasks and how much time they had to take off from work to attend planned or unplanned caregiving tasks. MethodsWe conducted 2 surveys to assess within-participant changes in outcomes for the unpaid, employed, caregivers after 6 weeks of using the mobile app (n=176) between March 30, 2020, and May 11, 2020. The surveys contained questions in three domains: the caregiver's support system, time use and perceived productivity, and perceived health and well-being. The results of the linear probability models are presented below. ResultsApp use was significantly associated with decreasing the probability of doing most caregiving tasks alone by 9.1% points (SE 0.04; P=.01) and increasing the probability of at least one person helping the primary caregiver by 8.0% points (SE 0.035; P=.02). App use was also associated with improving the time use of the primary caregiver who took significantly less time off work to attend to caregiving duties by 12.5% points (SE 0.04; P=.003) and decreased the probability of spending more than 30 hours weekly on caregiving by 9.1% points (SE 0.04; P=.02). Additional findings on the positive impact of the app included a decrease in the probability of reporting feeling overwhelmed by caregiving tasks by 12.5% points (SE 0.04; P=.003) and a decrease in the probability of reporting negative health effects by 6.8% points (SE 0.04; P=.07) because of caregiving. Although subjects reported that COVID-19 increased their stress attributed to caregiving and prevented them from requesting help for some caregiving tasks, using the app was still associated with improvements in receiving help and lessening of the negative effects of caregiving on the caregivers. ConclusionsApp use was associated with improvements in 7 of 11 caregiver outcomes across three main categories: their support system, time spent on caregiving, and perceived health and well-being. These findings provide encouraging evidence that the mobile app can significantly reduce caregiver burden by leveraging a caregiver's support network despite the additional challenges brought by COVID-19 on caregivers.